Unusual Presentations of Focal Periphyseal Edema Zones: A Report of Bilateral Symmetric Presentation and Partial Physeal Closure. (12th November 2015) - Beckmann, Nicholas; Spence, Susanna
Abstract : Focal periphyseal edema (FOPE) zones are areas of periphyseal edema seen near the time of physeal closure which are believed to be a physiologic phenomenon related to changes in distribution of forces around the physis as it closes. Since the original case series describing these areas of periphyseal edema, there has been little published in regard to FOPE zone outside of review articles. We present a set of three patients identified with focal periphyseal edema zones around the knee and compare our findings with the initial case series. We include a patient presenting with bilateral, nearly symmetric, focal periphyseal edema zones of the proximal tibia physis and a patient with partial closure of the physis at time of presentation, which were not reported in the original case series.